A Video Analysis of Use of the New ‘Concussion Interchange Rule’ in the National Rugby League - Gardner, A. J.; Iverson, G. L.; Stanwell, P.; Moore, T.; Ellis, J.; Levi, C. R. (International Journal of Sports Medicine, 2016)
The National Rugby League (NRL) in Australia introduced a new ‘concussion interchange rule’ (CIR) in 2014, whereby a player suspected of having sustained a concussion can be removed from play, and assessed, without an interchange being tallied against the player’s team. We conducted a video analysis, describing player and injury characteristics, situational factors, concussion signs, and return to play for each “CIR” event for the 2014 season. There were 167 reported uses of the CIR. Apparent loss of consciousness/unresponsiveness was observed in 32% of cases, loss of muscle tone in 54%, clutching the head in 70%, unsteadiness of gait in 66%, and a vacant stare in 66%. More than half of the players who were removed under the CIR returned to play later in the same match (57%). Most incidences occurred from a hit up (62%) and occurred during a tackle where the initial contact was with the upper body (80%). The new concussion interchange rule has been used frequently during the first season of its implementation. In many cases, there appeared to be video evidence of injury but the athlete was cleared to return to play. More research is needed on the usefulness of video review for identifying signs of concussive injury.
Keywords: concussion; video analysis; injury management; return to play